PENGARUH ORGANIZATIONAL LEARNING CAPABILITY TERHADAP INTELLECTUAL CAPITAL MELALUI ERP IMPLEMENTATION SEBAGAI VARIABEL MEDIASI - Dio Adi Hendrawan; Priskila Adiasih; Saarce Elsye Hatane (Business Accounting Review, 2017)
This study aims to determine the impact of organizational learning capability to intellectual capital through ERP implementation as a mediating variable in companies that have implemented ERP system in Indonesia. The population used in this study is a company in Indonesia that implements ERP system. The sample of this research is 36 companies in Indonesia that have implemented ERP system. Data analysis techniques used in this study is partial least square to describe the relationship between variables. Data processing using WarpPLS 5.0. The results showed that organizational learning capability with ERP implementation have a positive and significant effect on intellectual capital in companies that implement ERP system in Indonesia.